Indigenous chicken production system in different agro-ecology of Indian Himalayan Region: implication on food and economic security - Singh, Mahak; Patton, R. N.; Mollier, R. T.; Pongener, N.; Yadav, Rekha; Singh, Vinay; Katiyar, Rahul; Singh, G. D.; Deori, Sourabh; Doley, Sunil; Chaudhary, J. K.; Babu, Subhash; et al. (Frontiers in Nutrition, 2023)
The indigenous chicken production system (ICPS) has several use values and ecosystem services. In the last few years, ICPS has been recognized for its possible contribution to household food security, income generation, wildlife protection, and bettering the women’s lives. This study aimed to collect, for the first time, comprehensive information about ICPS in three different agro-ecologies (tropical, sub-tropical, and sub-temperate) of the Indian Himalayan Region (IHR) and its role in food and economic security of traditional communities. In this study region, ICPS is semi-extensive, providing homegrown feed and temporary night shelter. In sub-temperate agro-ecology, females owned non-significant (p = 0.170) more indigenous chicken flocks than males. Households in sub-temperate agro-ecologies had significantly (p ≤ 0.001) larger flock sizes and tropical livestock units (chicken-TLU). However, the livestock diversity index (LDI) was significantly higher (p ≤ 0.001) in tropical and subtropical agro-ecology. The households in the sub-temperate region highly (p ≤ 0.001) valued indigenous chicken because of its survivability and adaptability. In absolute numbers significant (p ≤ 0.001) higher numbers of adult birds died in past 1 year in sub-temperate agro-ecology. The mortality rate of adult birds in sub-temperate agro-ecology was 9%, and it was 14 and 15% in tropical and sub-tropical agro-ecologies, respectively. In sub-temperate agro-ecology, larger flock size translated into significantly higher (p ≤ 0.001) egg production and subsequently a significant (p ≤ 0.001) higher egg consumption per household per month. In sub-temperate agro-ecology, households’ dietary diversity score was significantly (p ≤ 0.001) higher. Similarly, the average annual income from ICPS was significantly higher (p ≤ 0.001) in sub-temperate agro-ecology and accounted for 18% of household income. ICPS’ marketing chain was relatively short in the sub-temperate region. In all agro-ecologies, indigenous chicken and egg demand was significantly higher (p ≤ 0.001) in the winter. ICPS litter is used as farmyard manure, enhancing ecological resilience. In all agro-ecologies, the three most frequently cited obstacles to extending the indigenous chicken production system are illnesses, predators, and a lack of chicks availability. ICPS contributes to food and nutritional security, economic stability, and ecological resilience in this hilly and fragile ecosystem. Even though the system is self-sustaining, management and health interventions can increase production and productivity.